$$y^{''} = k^2y,y(0)=A, y^{'}(0) = B$$

I used the characteristic equation and found that $r=k,-k$.

Then the general solution is $y(x) = C_1e^{kx}+C_2e^{-kx}$.

And $y^{'}(x) = C_1ke^{kx}-C_2ke^{-kx}$

Use the initial condition I got $A=C_1+C_2$ and $B=k(C_1-C_2)$

How do I express $C_1$ and $C_2$ in terms of $A$ and $B$? Did I do something wrong in my calculation?

  • $\begingroup$ You're doing fine. Two equations, two unknowns. $\endgroup$ – Ron Gordon Oct 1 '13 at 17:53
  • $\begingroup$ @RonGordon, how do I solve the equation so that I can express $C_1$ and $C_2$ explicitly in terms of $A$ and $B$? $\endgroup$ – user59036 Oct 1 '13 at 17:56
  • $\begingroup$ It is very peculiar that you would be dealing with differential equations without being able to solve two equation in two unknowns! You have two equations, $C_1+ C_2= A$ and $k(C_1- C_2)= B$. From the first equation, $C_2= A- C_1$ so the second equation can be written as $k(C_1- (A- C_1)= 2kC_1- kA= B$. $2kC_1= kA+ B$, $C_1= (kA+ B)/2k$. $\endgroup$ – user247327 May 1 '18 at 19:38

$$C_1+C_2=A$$ $$C_1-C_2=\frac{B}{k}$$

$$\implies 2 C_1 = A + \frac{B}{k}$$ $$\implies 2 C_2 = A - \frac{B}{k}$$



$A = C_1 + C_2 \tag{1}$


$B = k(C_1 - C_2) \tag{2}$

we have

$k^{-1}B = C_1 - C_2, \tag{3}$

assuming of course $k \ne 0$. Adding (1) and (3) yields

$2C_1 = A + k^{-1}B; \tag{4}$

subtracting them gives

$2C_2 = A - k^{-1}B, \tag{5}$

from which

$C_1 = \frac{1}{2}( A + k^{-1}B) \tag{6}$


$C_2 = \frac{1}{2}( A - k^{-1}B). \tag{7}$

Voila!!! $C_1, C_2$ in terms of $A$ and $B$!

Hope this helps! Cheerio,

and as always

Fiat Lux!!!


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.